PENERAPAN MODEL DISCOVERY LEARNING PADA MATERI PEMANASAN GLOBAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMA - Rosita, Windi; Zulhelmi, Zulhelmi; Sahal, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of the Discovery Learning model in improving students’ learning outcomes and to determine the differences in achievement between a class implementing the Discovery Learning model and a class using conventional instruction on the topic of Global Warming in Grade X at SMA Negeri 2 Tambang. The research employed a quasi-experimental method with a nonequivalent posttest only control group design. The sample consisted of 64 students divided into two classes, with 32 students in class X.7 as the experimental group and 32 students in class X.6 as the control group. The research instrument was a learning outcomes test comprising 20 multiple-choice questions developed based on Bloom’s Taxonomy cognitive levels (C1–C5). The data were analyzed using descriptive and inferential statistical techniques. The results showed that the experimental class achieved an average score of 82.03, categorized as good, while the control class obtained an average score of 75.78, also categorized as good. These findings indicate a significant difference in students’ learning outcomes between the experimental and control groups, demonstrating that the application of the Discovery Learning model effectively improves students’ learning outcomes on Global Warming material compared to conventional learning.